2018
DOI: 10.1128/jcm.01696-17
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Xpert MTB/RIF Results in Retested Patients with Previous Tuberculosis: Frequency, Profile, and Prospective Clinical Outcomes

Abstract: Globally, Xpert MTB/RIF (Xpert) is the most widely used PCR test for the diagnosis of tuberculosis (TB). Positive results in previously treated patients, which are due to old DNA or active disease, are a diagnostic dilemma. We prospectively retested sputum from 238 patients, irrespective of current symptoms, who were previously diagnosed to be Xpert positive and treated successfully. Patients who retested as Xpert positive and culture negative were exhaustively investigated (repeat culture, chest radiography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 24 publications
7
53
0
4
Order By: Relevance
“…It is important to note that these results were obtained from a limited number and variety of samples, as well as a few NTM species. In other studies in which GX-Ultra was used, the authors indicated that the increase in sensitivity with this new version came at the expense of a decrease in specificity, specifically in patients with a history of tuberculosis (13,27) and patients with meningitis (17). They hypothesized that the presence of DNA from MTUBC or intact bacilli could explain the reduction in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these results were obtained from a limited number and variety of samples, as well as a few NTM species. In other studies in which GX-Ultra was used, the authors indicated that the increase in sensitivity with this new version came at the expense of a decrease in specificity, specifically in patients with a history of tuberculosis (13,27) and patients with meningitis (17). They hypothesized that the presence of DNA from MTUBC or intact bacilli could explain the reduction in specificity.…”
Section: Discussionmentioning
confidence: 99%
“…One child in the probable TB group might have been correctly identified as an active TB case only by Xpert Ultra. In a second child, who was classified as "not TB" but had been treated for TB three years ago, Xpert Ultra might have detected MTB DNA only as remnant of a previous active TB episode 14,24 . However, cross-contamination or sample mix-up cannot be excluded.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, concerns about Xpert's specificity have been rising, as previous studies have reported false-positive errors in M. tuberculosis (11,12) and RIF resistance (13)(14)(15) detection in clinical practice. In some cases, false-positive RIF resistance results have been attributed to silent mutations within the RRDR of rpoB (13,14), or to a large cycle difference in the cycle threshold (C T ) value between any two probes (defined as ΔC T maximum values) (13,15).…”
mentioning
confidence: 99%